2011
DOI: 10.1029/2010wr009845
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact on meteorological, agricultural, and hydrological drought in central Illinois

Abstract: [1] This paper investigates the impact of climate change on drought by addressing two questions: (1) How reliable is the assessment of climate change impact on drought based on state-of-the-art climate change projections and downscaling techniques? and (2) Will the impact be at the same level from meteorological, agricultural, and hydrologic perspectives? Regional climate change projections based on dynamical downscaling through regional climate models (RCMs) are used to assess drought frequency, intensity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
117
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 36 publications
2
117
0
1
Order By: Relevance
“…In this study, we used the standardized precipitation index (SPI) (McKee et al, 1993), the standardized soil moisture index (SSWI) (Wang et al, 2011a(Wang et al, , 2011b) and the standardized runoff index (SRI) (Shukla and Wood, 2008) to characterize the meteorological, agricultural, and hydrological droughts respectively. The SPI is computed on the basis of probability distributions of precipitation for specified monthly time scales.…”
Section: Drought Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used the standardized precipitation index (SPI) (McKee et al, 1993), the standardized soil moisture index (SSWI) (Wang et al, 2011a(Wang et al, , 2011b) and the standardized runoff index (SRI) (Shukla and Wood, 2008) to characterize the meteorological, agricultural, and hydrological droughts respectively. The SPI is computed on the basis of probability distributions of precipitation for specified monthly time scales.…”
Section: Drought Analysis Methodsmentioning
confidence: 99%
“…These patterns are not confined to northern China only however. Indeed, Wu et al (2011) reconstructed China's daily soil moisture values from 1951 to 2009 and showed that up to 30% of the total area of China is prone to drought and Wang et al (2011aWang et al ( , 2011b showed that over the past 60 years severe droughts in China grew increasingly common, suggesting an increasing risk on sustainable agricultural productivity across the whole nation. Zou et al (2005) used the Palmer Drought Severity Index (PDSI) to investigate the variations in droughts over China, and Zhai et al (2010) used both PDSI and standardized precipitation index (SPI) to identify tendencies in dry/wet conditions during recent decades over ten large regions in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies (e.g., Pandey and Ramasastri 2001;Wang et al, 2011;Van Loon et al, 2012) were performed toward this purpose. Most of previous studies were conducted with the aid of hydrological models.…”
Section: Introductionmentioning
confidence: 99%
“…Through various numerical experiments, previous studies indicated that drought propagation is closely associated with local landscape and local climatic conditions . Wang et al (2011) used a hydro-agronomic model to study the propagation from meteorological drought to agricultural and hydrological droughts in central Illinois. Van Loon et al (2012) applied an ensemble mean of large-scale hydrological models to evaluate drought propagations.…”
Section: Introductionmentioning
confidence: 99%